THE ASSOCIATION OF EGFR AND ALBUMINURIA WITH SYSTOLIC HYPERTENSION IN PATIENTS WITH DIABETES. (June 2022) - Georgianou, E.; Markakis, K.; Georgianos, P.; Zografou, I.; Sachinidis, A.; Sabanis, C.; Doumas, M.
Abstract : Objective: Large epidemiological studies have shown that the prevalence of hypertension increases in parallel with the staging of chronic kidney disease. However, it remains unclear whether the decline in estimated-glomerular-filtration-rate (eGFR) or the severity of albuminuria is a stronger determinant of systolic hypertension. Design and method: In 483 outpatients with diabetes, the eGFR was determined using the CKD-EPI equation and albuminuria was assessed by measuring the albumin-to-creatinine ratio (ACR) in a random urine specimen. Triplicate automated office blood pressure (BP) recordings were obtained with the validated device HEM-705 (Omron, HealthCare) under standardized conditions requiring an at least 5-minute seated rest period in a quiet room. Results: The average office systolic BP was 138.3 ± 19.4 mmHg, whereas 69.6% of the patients were being treated with an average of 2.2 ± 1.1 antihypertensive medications daily. In univariate linear regression analysis, office systolic BP was associated with age, body mass index (BMI), antihypertensive drug use, the number of prescribed antihypertensive medications, severity of albuminuria and decline in eGFR. In multivariate analysis, however, it was logUACR (P = 0.022) and not eGFR (P > 0.05) the factor that remained a significant determinant of office systolic BP. Other parameters associated with office systolic BP in the multivariate model were higher age (P = 0.014), BMI (P = 0.012) and the number of prescribed antihypertensive medications (P = 0.045). Conclusions: The present study suggests that the severity of albuminuria and not the decline in eGFR is possibly a stronger determinant of systolic hypertension in patients with diabetes.